Optimization of Digital Marketing Strategy with Implementation of SOSTAC Method - Jesi Irwanto; Wahyuning Murniati; Anisatul Fauziyah (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This training aims to develop digital marketing strategies for pesantren cooperative business entities as one of the efforts in countering the impact of the COVID 19 Pandemic.